Dengue fever and thrombocytopenia – A prospective Observational Study at Tertiary Care Centre - Tulara, Neeraj Kumar (Eastern Journal of Medical Sciences, 2019)
Background: Dengue fever is one of the commonest diseases in tropical countries and carries significant morbidity and mortality. Thrombocytopenia (low platelets) is one of the very common manifestations in case of dengue infection. Platelet transfusion in dengue always remains controversial. Objective: Present study was conducted to study precise criteria and transfusion trigger for platelet transfusion in our set-up. Materials and Methods: This study was conducted on 112 serologically antibody positive confirmed dengue patients admitted in a Hospital, Powai, Mumbai, between 1st of August to 30th October 2017. The age groups of the included patients were within 20-50 years and did not have any co morbidity and were diagnosed at OPD. Indication for hospitalization includes high grade fever (>101° F) and platelet counts less than 100,000 along with other viral prodromal symptoms. Clinical data, reports of laboratory investigations, platelets requirements and data obtained from daily follow-up and record sheets were analyzed. Results: In the serologically positive confirmed cases, the prevalence of thrombocytopenia (count